2021
DOI: 10.1002/emp2.12595
|View full text |Cite
|
Sign up to set email alerts
|

Predicting 30‐day return hospital admissions in patients with COVID‐19 discharged from the emergency department: A national retrospective cohort study

Abstract: Objectives: Identification of patients with coronavirus disease 2019 (COVID-19) at risk for deterioration after discharge from the emergency department (ED) remains a clinical challenge. Our objective was to develop a prediction model that identifies patients with COVID-19 at risk for return and hospital admission within 30 days of ED discharge. Methods:We performed a retrospective cohort study of discharged adult ED patients (n = 7529) with SARS-CoV-2 infection from 116 unique hospitals contributing to the Na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…In the series by Somani et al, 3.8% of patients were readmitted within 14 days 9 and 7.6% within 30 days in the study by Beiser et al 10 These two studies reported registries of patients cared for in-hospital, but without any mention of early discharge and without the need for continued home care.…”
Section: Discussionmentioning
confidence: 99%
“…In the series by Somani et al, 3.8% of patients were readmitted within 14 days 9 and 7.6% within 30 days in the study by Beiser et al 10 These two studies reported registries of patients cared for in-hospital, but without any mention of early discharge and without the need for continued home care.…”
Section: Discussionmentioning
confidence: 99%
“…Several prior studies used longer intervals including 7, 13 , 16 14, 14 or even 30 days. 5 , 7 , 10 , 12 We felt that a rule predicting outcomes within 72 hours of ED assessment might convey a more appropriate assessment of immediate risks that might be mitigated with decisions made in the ED, specifically around the decision to admit at the index visit. The 72‐hour interval is commonly used as a health care quality metric for patient recidivism.…”
Section: Discussionmentioning
confidence: 99%
“… 1 , 2 , 3 , 4 Prior work has identified several clinical factors associated with progression to severe COVID‐19 disease. 5 , 6 , 7 , 8 , 9 , 10 The application of these findings to individual patients to support bedside decision‐making is not intuitive. Clinical decision rules (CDRs) involve the transformation of observed associations between various clinical features and outcomes into a “rule” or score that can be used to risk‐stratify patients and directly support bedside clinical decision‐making with individualized risk estimates.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective study during the first three months of the pandemic found that approximately 9% of these patients had another unscheduled ED visit within 72 hours [8]. Similarly, a multicenter study aimed at developing a predictive model for identifying those at risk of a return visit and hospitalization found that 21% of patients had returned to the ED by 30 days from the index ED visit [9]. Unfortunately, the design of these studies precluded the determination of what percentage of repeat visits were related to COVID-19 or what factors may have been responsible for the high rate of return (e.g., worsening symptoms, inadequate follow-up, and anxiety).…”
Section: Introductionmentioning
confidence: 99%